2016
DOI: 10.1371/journal.pone.0168755
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Kidney Preservation Solutions Prior to Renal Transplantation

Abstract: One of the main issues in kidney transplantation is the optimal functional preservation of the organ until its transplantation into the appropriate recipient. Despite intensive efforts, the functional preservation period remains limited to hours. During this time, as a result of cellular injury, various proteins, peptides, and other molecules are released by the organ into the preservation medium. In this study, we used proteomic techniques to analyze the protein profiles of preservation solutions in which org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Understanding these aspects in the context of donor organ function warrants further investigation. proteomics analysis performed by Coskun et al (2016), who found secretion of cytoskeletal proteins of DBD donor kidneys during SCS. However, they did not include transplant outcome into their analysis [24].…”
Section: Discussionmentioning
confidence: 99%
“…Understanding these aspects in the context of donor organ function warrants further investigation. proteomics analysis performed by Coskun et al (2016), who found secretion of cytoskeletal proteins of DBD donor kidneys during SCS. However, they did not include transplant outcome into their analysis [24].…”
Section: Discussionmentioning
confidence: 99%
“…Both HSP70 and HSP90 were rapidly induced in the cytoplasm of injured epithelial cells of the proximal tubules during the degenerative and regenerative phases of the post-ischemic injury. In the study of Coskun et al (2016), the members of HSP70 and HSP90 families were detected in the preservation solution of the pretransplanted kidney by proteomic analysis. Furthermore, the levels of HSP90β and HSP70 were correlated with ischemia time and donors' age.…”
Section: Interplay Of Hsps In Kidney Diseasesmentioning
confidence: 99%
“…Furthermore, a strong association between chronic graft injury and overexpression of complement components has been found by proteomic analysis in kidney donor biopsies (62). These results indicated that shorter periods of ischemia are clearly associated with less complement activation; in addition, the protein profiles of preservation solutions in which kidney from deceased donors had been stored revealed intense activity of complement effectors (as C3, factor B) during organ storage preceding transplantation (63).…”
Section: The Role Of Complement In Irimentioning
confidence: 86%